A STUDY: ON PREMARITAL SEXUAL HEALTH BEHAVIOR AMONG THE ADOLESCENT GIRLS IN INDIA - Pal, Manisha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper reviews documents that have influenced understanding of premarital sexual health behavior among the adolescent girls in, India. Focus is on premarital sexual behavior and practices among the adolescent groups, which is comparatively raised in India from the last decades, especially in urban areas. In present scenario adolescents are more sexually active than ever before. Among adolescent who are at early age fourteen or younger are more sexually active and faces innumerable health risk due to their unsafe practices. They are more likely to get involved in high-risk sexual behaviors that comprises unprotected sex, unwanted pregnancies, abortions, having multiple or high-risk partners, raping a partner, and being intoxicated while having sex, alcohol and drug abuse, stealing, violence, and poor performance in school etc. There are many frequently follow romantically driven decisions on sexual relationships like sexually transmitted diseases unwanted pregnancies, abortions, and other related health problems (Hurissa.et.al. 2014). Premarital sexual health behaviour of adolescents in India is a multifaceted and growing problem, influenced by cultural norms, socio-economic factors and transforming social behaviour. The teenage years are a time of great change, both physically and emotionally, and for some young people it will also be a time when they will begin to explore their sexuality. In India, however, there is little discourse about sexual health, and many face stigmas surrounding premarital sexual behavior, which often leaves adolescents without reliable sexual health education. Yet without proper education and resources it can often lead to dangerous activity, unwanted pregnancies and a greater level of STIs which has lasting effects on youth health, education and future opportunities. For effective health promotion among this age group, knowledge of premarital sexual health behaviour among adolescents is crucial to point out the challenges adolescent face and to identify areas where much efforts can be taken to overcome the problems faced by adolescents. This enables policymakers, educators, and health professionals to create culturally appropriate programs effectively teaching adolescents about risk prevention, consent, and healthy relationships. In addition, the promotion of comprehensive sexual education can empower young people to make informed decisions, thus mitigating the health risks arising from the stigma and misinformation. Dealing with adolescent sexual health in a proactive approach with no blame leads to individual well-being, pivotal in promoting public health and social development of the country. On the basis of deeper and critical investigation into the literature, the study found that. This paper will explore and examines the reasons for. It also suggests the immediate action to achieve.